Internet medievalism and the White Middle Ages - Elliott, Andrew B. R. (History compass, 2018)
The Middle Ages, and ideas about modern culture drawn from or rooted in the medieval period, have found themselves recurring with alarming frequency within recent political discourse. From President Bush's crusade rhetoric surrounding the War on Terror to the Far Right's location of White nationalism within an ongoing framework of medieval nation-founding, the past has increasingly been used in the service of the present. In their more egregious forms—such as the rise of White supremacist movements in Europe, the USA, and Australia and their amalgamation into mainstream political discourse—the use of medieval national and cultural memories has led to a whitewashing of the medieval past. This article argues that these instances of medievalism are not simply inaccuracies but come about through a recirculation of vague ideas about the Middle Ages through online in-groups. Consequently, such political uses of the medieval past are often what have been termed "banal" medievalisms in the sense that they are not always intended as deliberate references to history by useful appropriations in the service of the present.